Crack detection in a simply supported RC beam using simplified Laplacian - Razak, H.A.; Teng, S.L.; Ismail, Z.; Abdul Rahman, A.G. (2001)
This paper describes the detection and identification of cracking severity in a reinforced concrete beam using modal data. Experimental modal test was performed on the beam before and after application of load of increasing intensity to induce a single crack at a fixed location. Modal parameters extracted were categorised into two groups, namely local response parameter (mode shape data) and global response parameters. Localised changes such as cracking reduce the stiffness of the structure, and therefore caused a localised change in the discrete function of the mode shape. From a previous research, Laplacian Operator was initially proposed. However, when applied to a non-homogeneous and composite material such as reinforced concrete, the operator was too sensitive and did not yield meaningful results. Hence, a simplified Laplacian operator was suggested. In this investigation, it was found that global response such as natural frequency is a good indicator to detect the occurrence of the deterioration in the structure. However, the local response data such as mode shape was required to detect the defect location accurately and a simplified Laplacian operator worked quite successfully. Furthermore, it was observed that the higher frequency modes tend to detect the occurrence of cracking in the earlier stages.